Development of monopoly learning media based on joyful learning model on natural sciences and social material - Hafida Rahma; Sri Sami Asih (Universitas Muhammadiyah Malang, 2024)
The background of this research is the low learning outcomes of students in the content of science lessons on force material and its influence on everyday life. In addition, the use of learning media by teachers is still very limited and there is no development of learning models carried out. This researche aimed to develop motivation and learning outcomes of students grade IV. The type of research used in this study is research and development or Research and Development (R&D) which uses a research model design from Borg and Gall. This research resulted in four things, including: 1) Development of worksheet learning media in science learning force material; 2) The feasibility of media products that are considered very valid by experts with a final validation average of 91%; 3) Student responses to worksheet joyful learning media are very valid with a percentage of scores of 93.5%, 4) t-test results show GIS (2-tailed0 0.00 < 0.05 which shows an increase in average results before and after treatment on small-scale tests and large-scale tests, so it can be concluded that worksheet joyful learning media can improve student learning outcomes in the force material of grade IV elementary school students (natural sciences and social).